1980
DOI: 10.1021/jf60232a069
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of unfrozen and free water in soy proteins by differential scanning calorimetry

Abstract: Soy isolates, soy concentrate, soy flour, and ovalbumin were analyzed for amounts of unfrozen water at different total moisture contents. Analysis was by differential scanning calorimetry to determine heats of fusion and integral heats of vaporization. Unfrozen water did increase with increased total water content. When plotted against total moisture (dry basis), the unfrozen water was a linear function of total water above a concentration of 1 g of water/g of solids, and ~10% of added water was unfrozen. Plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 2 publications
2
18
0
Order By: Relevance
“…Differential thermal analysis (DTA) and differential scanning calorimetry (DSC) are two recently-developed techniques available to the food industry for multi-purpose uses. DTA was used by Duckworth [9], Parducci and Duckworth [10] and Bushuk and Mehrotra [11,12], while Ross [5], Karmas and Chen [13], Muffet and Snyder [14], Kumagai et al [15], Roos [6,16,17], Lovric et al [18], Heinevetter et al [19], Roos and Karel [20] and Wang and Kolbe [21] applied DSC to determine the free and bound water contents of different food products and biological materials.…”
Section: Introductionmentioning
confidence: 99%
“…Differential thermal analysis (DTA) and differential scanning calorimetry (DSC) are two recently-developed techniques available to the food industry for multi-purpose uses. DTA was used by Duckworth [9], Parducci and Duckworth [10] and Bushuk and Mehrotra [11,12], while Ross [5], Karmas and Chen [13], Muffet and Snyder [14], Kumagai et al [15], Roos [6,16,17], Lovric et al [18], Heinevetter et al [19], Roos and Karel [20] and Wang and Kolbe [21] applied DSC to determine the free and bound water contents of different food products and biological materials.…”
Section: Introductionmentioning
confidence: 99%
“…Schnepf (2) reviewed the types of bonding between water and protein molecules, and how their interaction relates to these functional properties. Numerous methods for assessing protein hydration include dielectric studies (3), nuclear magnetic resonance (4)(5)(6)(7)(8) and calorimetry (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…In fact, an endothermic peak around 0°C, which would correspond to the melting of crystallizable (unbound) water, was not observed. Thus, it was concluded that the water molecules situated in the feathermeal were bound to the protein macromolecules 15…”
Section: Resultsmentioning
confidence: 99%